Інституціональні детермінанти розвитку інновацій в агропромисловому виробництві - Гончаренко, Оксана Володимирівна; Honcharenko, Oksana; Самілик, Тамара Миколаївна; Samilyk, Tamara; Теслюк, Юлія Валеріївна; Teslyuk, Julia (Дніпровський державний аграрно-економічний університет, 2019)
У статті визначені інституціональні детермінанти та здійснено оцінку стану нституціонального забезпечення розвитку інновацій в агропромисловому виробництві. Теоретико -методологічною основою дослідження є системний підхід до дослідження інституціонального забезпечення розвитку інновацій в гропромисловому виробництві. Констатовано, що реальному запровадженню інноваційного розвитку агропромислового виробництва протидіє нестабільність і неефективність нормативно-правового регламентування, відсутність дієвого інфраструктурного й організаційно-економічного забезпечення галузі. Встановлено, що формування інституціонального забезпечення інноваційного розвитку пов’язане зі створенням ефективних інститутів й інституцій. Критерієм ефективності є умова набуття сукупністю інститутів й інституцій ознак системності, комплементарності. Аргументовано, що інституціоналізація інноваційного розвитку є процесом формування й функціонування базисних й інноваційних інститутів та інституцій. Визначено,що реалізація обґрунтованих альтернативних сценаріїв інноваційного розвитку має базуватись на відповідній концепції, яка націлена на оптимізацію ресурсів, акумулювання територіальних потенціалів і резервів, координацію і збалансування внутрішньогалузевих й міжгалузевих взаємодій. Теоретичні та методологічні положення поглиблюють практичні засади інституціонального забезпечення розвитку інновацій в агропромисловому виробництві. The article identifies institutional determinants and assesses the stat e of institutional support for the development of innovations in agro-industrial production. The theoretical and methodological basis of the research is a systematic approach to the research of institutional support for the development of innovations in agro-industrial production. Structural and functional analysis was used to identify institutional determinants and justify the elements of institutional support. It is stated that the real introduction of the innovative development of agro-industrial production is counteracted by the instability and inefficiency of the regulatory and legal regulation, the lack of effective infrastructure and organizational and economic support of the industry. The introduction of institutional design with creation of transitional forms of agronomy realization, strategic planning and programming of innovative development, infrastructure support of innovation transfer is substantiated. It is established that the formation of institutional support for innovative development is associated with the creation of effective institutions and institutions. The criterion of efficiency is the condition of acquiring a set of institutions and institutions of signs of systematic, complementary. It is argued that the institutionalization of innovation development is the process of formation and functioning of basic and innovative institutions and institutions. It is determined that the implementation of sound alternative scenarios of innovative development should be based on the appropriate concept, which is aimed at optimization of resources, accumulation of territorial potentials and reserves, coordination and balancing of intra-industry and inter-industry interactions. It is proved that the success and efficiency of the conceptual model implementation is achieved by the minimum number of coordination stages, as well as the decision-making centers; specification of contribution and resources, elements and subsystems in their conceptual unity. Theoretical and methodological provisions deepen the practical foundations of institutional support for the development of innovations in agro-industrial production.
Institutional determinants of innovation development in agricultural production
Keywords: агропромислове виробництво; agro-industrial production; інновація; innovation; інноваційний розвиток; innovative development; інноваційна політика; innovation policy; інституціоналізація; institutionalization